Reduced activity of ATP synthase in mitochondria causes cytoplasmic male sterility in chili pepper - Li, J.; Pandeya, D.; Jo, Y.; Liu, Wing Yee; Kang, B. (2013)
Cytoplasmic male sterility (CMS) is a maternally inherited trait characterized by the inability to produce functional pollen. The CMS-associated protein Orf507 (reported as Orf456 in previous researches) was previously identified as a candidate gene for mediating male sterility in pepper. Here, we performed yeast two-hybrid analysis to screen for interacting proteins, and found that the ATP synthase 6 kDa subunit containing a mitochondrial signal peptide (MtATP6) specifically interacted with Orf507. In addition, the two proteins were found to be interacted in vivo using bimolecular fluorescence complementation (BiFC) and co-immunoprecipitation (Co-IP) assays. Further functional characterization of Orf507 revealed that the encoded protein is toxic to bacterial cells. Analysis of tissue-specific expression of ATP synthase 6 kDa showed that the transcription level was much lower in anthers of the CMS line than in their wild type counterparts. In CMS plants, ATP synthase activity and content were reduced by more than half compared to that of the normal plants. Taken together, it can be concluded that reduced ATP synthase activity and ATP content might have affected pollen development in CMS plants. Here, we hypothesize that Orf507 might cause MtATP6 to be nonfunctional by changing the latter’s conformation or producing an inhibitor that prevents the normal functioning of MtATP6. Thus, further functional analysis of mitochondrial Orf507 will provide insights into the mechanisms underlying CMS in plants.